Effectiveness of daily interruption of sedation in sedated patients with mechanical ventilation in ICU: A systematic review - Hong-Bo Chen; Jun Liu; Li-Qin Chen; Gong-Chao Wang (Elsevier, 2014)
Purpose: To evaluate the effectiveness of daily sedation interruption in patients with mechanical ventilation in intensive care unit (ICU). Methods: The randomized controlled trials (RCTs) on the application of daily interruption of sedation in sedated patients with mechanical ventilation in ICU were collected through databases including Cochrane library, MEDLINE, Web of Knowledge, Embase, CNKI, CBM and VIP Data. Two reviewers independently assessed the quality of studies and extracted the data. Meta-analysis was conducted on the included studies. Results: Eight RCTs involving 757 patients were included. The daily sedation interruptions could shorten the duration of mechanical ventilation (Z = 5.36, p < 0.0001), length of stay (Z = 2.93, p = 0.003 < 0.05) and reduce the rate of tracheotomy (Z = 3.97, p < 0.00001) in these patients. Additionally, daily sedation interruption was not associated with increased rate of unplanned extubation by the patients (Z = 0.53, p = 0.6 < 0.05). Conclusion: The application of daily interruption of sedation in patients with mechanical ventilation in ICU is safe and effective.